Photocatalytic activity of nanostructured TiO2 thin films prepared by pulsed spray pyrolysis - López, Alcides (2006)
Nano-structured TiO2 thin films were deposited onto soda lime glass by the pneumatic spray pyrolysis method from a peroxo-titanium complex solution. Samples were prepared spraying 10 s the complex solution followed by an interruption of 20 s in order to avoid inadequate substrate cooling, the substrate temperature was varied from 230 to 430 °C in 50 °C steps. Amorphous as-deposited films crystallized to the anatase phase after an annealing process at 500 °C for 3 h. The photocatalytic activity of the nanostructured TiO2 thin films was studied under UV irradiation with the degradation of methylene-blue. Amorphous as-deposited TiO2 films prepared at low substrate temperatures (280 °C) showed the best photocatalytic activity, but after the annealing process films exhibit a decrease in the photocatalytic activity due to both the increase in the grain size and the decrease in the surface area.